Colors for optimal thermal comfort in university study hall - interdisciplinary theoretical and practical studies. Issue 1 (October 2020) - Marinova, I; Ivanova, A
Abstract: Improving thermal comfort trough interior color design is a contemporary energy efficiency and healthy living environment tendency. The article considers scientific-applied task of choosing a color design for a specific university seminar hall. The concept integrates areas of architecture and design, color science, physics, chemistry, material science, psychology, ect., in the context of aesthetics, light-reflecting qualities and physical and emotional impact of colors upon inhabitants. Optimal color design considers general principles applied to a specific environment and requires integrated approach and interdisciplinary theoretical and practical studies in order to improve the process of creating such an optimal solution. The report examines contemporary interior color design scope. Characteristics of university hall and the requirements they raise are studied. An overview of colors' features as a means of improving thermal comfort is included. Stages of the design process and the involved specialists are listed. The advantages of nonlinear design process are applied. As result the succession and the degree of participation of different science fields specialists in the interdisciplinary theoretical and practical studies and in the choice of the final design are set.